Analisis Partisipasi Masyarakat dan Sumber Daya Olahraga - Hardiyo Simbayan; Meri Haryani; Andika Maili; Safri Irawan; Nadia Aqila Kaltsum Hamzah (Universitas Negeri Padang, 2025)
This study aims to analyze the level of community participation and the availability of sports resources in Isimu Village, Tibawa District, Gorontalo Regency. This research is important to identify factors that influence community participation in sports activities and the availability and quality of sports resources in the village. In general, this study aims to uncover the challenges and opportunities in developing community-based sports in Isimu Village. Previous research has shown that community participation in sports activities can be influenced by various factors, including available facilities, education level, and social support. Data were collected from 53 randomly selected respondents through a questionnaire that measured the level of participation in sports, as well as perceptions of sports facilities and instructor support. The results showed that although 71.7% of respondents had exercised in the past 3 months and 54.7% exercised regularly, 62.3% of respondents considered the sports facilities in the village inadequate. Furthermore, 67.9% of respondents stated that the lack of instructors or coaches was a major barrier to sports participation. This study concluded that improving sports facilities and providing competent instructors is urgently needed to increase community participation in sports, which in turn will have a positive impact on the health and fitness of the village community.